Case Study: Drug Therapy Monitoring in a Patient with Abdominal Colic at a Regional Public Hospital in Gorontalo - Papeo, Dizky Ramadani Putri; Mamu, Safira Mahadewi; Putri, Eka Fadhila; Irmayanti, Irmayanti; Laurina, Nur Fadhilah; Daud, Nurfitrah Ramdawati (Jambura Medical and Health Science Journal, 2026)
Abdominal colic is a common complaint of abdominal pain frequently observed in hospitalized patients, often associated with gastrointestinal infections. This study aims to evaluate the rationality of antibiotic use and identify potential Drug-Related Problems (DRPs) in patients with abdominal colic. The report was conducted descriptively using a SOAP-based approach, utilizing inpatient medical record data at Gorontalo City General Hospital in February 2025. The case analysis showed that the use of ceftriaxone adhered to the 5R principles (right indication, right patient, right drug, right dose, and right duration). However, the concurrent administration of Fiocilas (ampicillin–cloxacillin) represented an unnecessary duplication of antibiotic therapy that was not supported by clinical indications or culture data. This was categorized as “unnecessary drug therapy” and posed a potential risk for antimicrobial resistance and adverse effects. The recommended pharmaceutical intervention was discontinuation of the additional antibiotic and continuation of the main therapy with clinical monitoring. To conclude, this case emphasizes the important role of pharmacists in monitoring the rational use of antibiotics to improve the safety and effectiveness of patient treatment.Keywords: Abdominal colic, abdominal pain, drug interactions, drug rationality, pharmacotherapy